Dynamic Changes in Aortic Stiffness after Substantial Weight Loss by Laparoscopic Sleeve Gastrectomy in Patients with Obesity: A 1-Year Follow-Up Study. (August 2021) - Gul, Murat; Inci, Sinan; Aktas, Halil; Yildirim, Oguz; Alsancak, Yakup; Ozkan, Namik
Arterial stiffness has been identified as a powerful and independent risk factor for cardiovascular disease. Obesity is associated with an increased risk of aortic stiffness (AS) and adverse cardiovascular events. Herein, we aimed to evaluate the effects of weight loss after laparoscopic sleeve gastrectomy (LSG) on AS in individuals with morbid obesity by using the transthoracic echocardiography (TTE). A total of 53 patients with obesity (17 males, 36 females) who underwent LSG and did not have any known heart disease were included in the study. The AS parameters were measured with TTE. The demographic and echocardiographic data of the patients were studied before, at 1 month and 12 months after surgery. The mean age of the study group was 34.41±11.62, 68% of whom were female. There were no significant differences in terms of the standard echocardiography and Doppler measurements as compared with preoperative values (all p>0.05). When the elastic parameters of the aorta were compared, no significant differences were detected regarding aortic strain (%) ((16.28±4.11) vs (16.68±4.56), p=(0.998)), distensibility (cm 2 /dyn) ((6.74±1.78) vs (7.03±2.31), p=(0.997)) and Aortic Stiffness Index values ((10.73±3.84) vs (10.63±3.34), p=0.998) between baseline and first month after surgery. In the 12-month follow-up, it was determined that the aortic strain ((16.28±4.11) vs (22.74±5.79), p≤0.001) and distensibility ((6.74±1.78) vs (10.34±3.059), p<0.001)) values increased at significant levels. Weight loss by LSG improves arterial stiffness parameters in patients with obesity over a 1-year follow-up.